2013
DOI: 10.7860/jcdr/2013/5477.2969
|View full text |Cite
|
Sign up to set email alerts
|

Household Salt Iodine Content Estimation with the Use of Rapid Test Kits and Iodometric Titration Methods

Abstract: Background: Universal salt iodization remains the best strategy for controlling iodine deficiency disorders in Nepal.Aims: This study was designed to study the salt types and the household salt iodine content of school aged children in the hilly and the plain districts of eastern Nepal. Material and Methods:This cross-sectional study was carried out on school children of seven randomly chosen schools from four districts, namely, Sunsari, Dhankuta, Sankhuwasabha and Tehrathum of eastern Nepal. The school childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…According to the rapid test kits (RTK) implemented during DHS, and often used in Cambodia, three out of four of the samples tested positive to iodine. A study in Nepal confirmed the accuracy of rapid test kits as a qualitative tool [ 25 ]; other tools are available to quantitatively determine salt iodine levels [ 26 ]. We could therefore extrapolate that the DHS was detecting a large amount of salt with levels of iodine that were insufficient to have a significant impact on UIC.…”
Section: Discussionmentioning
confidence: 99%
“…According to the rapid test kits (RTK) implemented during DHS, and often used in Cambodia, three out of four of the samples tested positive to iodine. A study in Nepal confirmed the accuracy of rapid test kits as a qualitative tool [ 25 ]; other tools are available to quantitatively determine salt iodine levels [ 26 ]. We could therefore extrapolate that the DHS was detecting a large amount of salt with levels of iodine that were insufficient to have a significant impact on UIC.…”
Section: Discussionmentioning
confidence: 99%
“…The salt sample was titrated by sodium thiosulfate whose amount was directly proportional to the amount of free liberated iodine. Starch was used as an indicator to mark the end-point of the titration by producing a blue color [20].…”
Section: Measurements Of Iodine In Saltmentioning
confidence: 99%
“…2.0 mL of starch paste was added again and the color changed to purplish blue. Titration was continued until the disappearance of the blue purple color (Sullivan et al, 1995;Nepal et al, 2013). This assay was repeated five times for each sample, and for the control sample of salt (iodized salt sample at 40 ppm, bought from the Directorate of Food and Applied Nutrition of Benin).…”
Section: Iodine Content By Iodometric Titrationmentioning
confidence: 99%